2022
DOI: 10.1016/j.btre.2021.e00696
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose, maltodextrin and inulin efficacy as cryoprotectant, preservative and prebiotic – towards a freeze dried Lactobacillus plantarum topical probiotic

Abstract: Highlights Saccharides assessed as combined cryoprotectant, preservative and prebiotic. Application is freeze dried topical probiotic of Lactobacillus plantarum . Inulin was best as cryoprotectant, but did not protect cells over storage. Best combined performance using sucrose with storage at 4 °C. Room temperature storage only feasible with skimmed milk (positive control).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 34 publications
(46 reference statements)
1
13
0
1
Order By: Relevance
“…The lyophilization process is the most common way to keep bacteria in an inactivated form to avoid losing colony-forming units (CFU) during a long storage period. This method also enables keeping adequate living probiotics for later use [ 77 , 78 ]. However, this process can damage the structure of probiotic bacteria cells (see Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The lyophilization process is the most common way to keep bacteria in an inactivated form to avoid losing colony-forming units (CFU) during a long storage period. This method also enables keeping adequate living probiotics for later use [ 77 , 78 ]. However, this process can damage the structure of probiotic bacteria cells (see Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Maltodextrin has been added as drying aid in drying process of several products such as in infrared drying of avocado pulp [2], freeze drying of Lactobacillus plantarum [10], and spray drying of soybean oil [11]. It was reported that together with sucrose and inulin, maltodextrin act as cryoprotectant, preservative and prebiotic in freeze drying process of L. plantarum, while maltodextrin provide a beneficial in avoiding the reduction of total polyphenols, total chlorophylls, and antioxidant activity as well as minimizing of lipid oxidation in avocado pulp [2], [10].…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that these cryoprotectants may serve also as potential prebiotics in topical applications. 19 There are numerous references to the benefits of applying living Lactobacillus to the skin, particularly to troubled skin. Some of the earliest references examined the ability of topically applied Lactobacillus to improve burns.…”
Section: Introductionmentioning
confidence: 99%
“…These low molecular weight oligosaccharides help to maintain the integrity of the microbial cell walls and keep the microorganisms intact and living in the powdered form. It has been suggested that these cryoprotectants may serve also as potential prebiotics in topical applications 19 . There are numerous references to the benefits of applying living Lactobacillus to the skin, particularly to troubled skin.…”
Section: Introductionmentioning
confidence: 99%